Resistance, professional agency and the reform of education in England (UCL Press, 2020)
Much research into structural reform in education has reported on the success or failure of individual projects. Less attention has been paid to how the discourses associated with reform are normalized in teachers' and head teachers' thinking, and realized in their actions. In this article, we engage with resistance at the interface of legal policy positioning and position-taking by educational professionals. Drawing on empirical data from an ethnographic study of structural change in a school in England, we deploy the metaphor of 'the Borg' to develop new insights into the different stances that educational professionals can take to avoid assimilation into a hive mind.